Evaluation of the Cyber Security Provision System for Critical Infrastructure - Jacek Jarmakiewicz; Krzysztof Maślank; Krzysztof Parobczak (Journal of Telecommunications and Information Technology, 2015)
The paper presents an assessment of the functional mechanisms that are part of the security system for the power grid control. The security system, its components, and the real time processes for the control of electricity supply were defined. In particular, SCADA protocols used in the control system and mechanisms for transferring them between the control center and actuators were identified. The paper also includes presentation of a test environment that is used for developed security mechanisms evaluation. In the last fragment of the paper, the test scenarios were formulated and the results obtained in the cyber security system were shown, which cover security probes reaction delay, forged malicious IEC 60870-5-104 traffic detection, DarkNet and HoneyPot interception of adversary actions, and dynamic firewall rules creation.